Ectopic non functional pituitary adenoma – A case report (Indian Journal of Case Reports, 2020)
Ectopic pituitary adenoma comprises 1–2% of all pituitary adenomas with a slight female predominance. Cases have been reported in the sphenoid sinus, cavernous sinus, parasellar region, nasal cavity, clivus, nasopharynx, and third ventricle. Here, we report the case of a 48-year-old female patient who presented with a 2 years history of nasal obstruction, epistaxis, and headache. The patient underwent necessary hematological, biochemical, and radiological investigations. Magnetic resonance imaging brain with angiography study showed a large soft-tissue mass in nasopharynx eroding the clivus and extending to involve bilateral sphenoid sinuses and parasellar region. The airway was also compromised. The pituitary gland appeared normal. All hematological and biochemical investigations were within normal limits. An endoscopic biopsy was also done. Tissue was submitted for histopathological examination and a diagnosis of pituitary adenoma was given. The patient had uneventful post-operative recovery and regularly came for follow-up.